The influence of enjoyment and love of music and high school music experience on music societies participation among non-music major college students in Sichuan, China: The mediating effect of basic psychological needs - Gu, Yuena; Hamid, Junainah Abd; Tham, Jacquline (International Journal of Innovative Research and Scientific Studies, 2025)
This study explored the influencing factors of non-music college students' participation in music societies in Sichuan, China, and analyzed the relationships between students' enjoyment and love of music (EALM), high school music experience (HSME), basic psychological needs (BPN), and music societies participation (MSP) and the mediating role of BPN. The study used a cross-sectional survey with an online questionnaire for 499 students and structural equation modeling to analyze the data. The results showed that EALM was the primary factor influencing MSP, with a significant direct positive association; HSME had a non-significant direct effect on MSP, but its fully mediated effect through BPN was significant; and BPN had a strong positive direct effect on MSP and partially mediated the relationship between EALM and MSP. The study suggests that the core motivation for non-music majors to participate in music societies is an intrinsic love of music, and that the high school music experience indirectly facilitates participation in music societies by fulfilling BPN (autonomy, relatedness, and competence). It is recommended that music education administrators and club activities should focus on stimulating the love of music, satisfying psychological needs, and optimizing the design and promotion of activities to enhance the participation of non-music majors.